Point of Sales Menggunakan Metode Agile Development pada Bengkel Mandala Motor - Andriansyah Utomo; Agung Triayudi; Ira Diana Sholihati (KITA Institute, 2023)
The development of the current Point of Sales (POS) system is very important for industry, especially for trading efforts, many business industries use digital recording or data collection systems. Mandala Motor Workshop is company engaged in the automotive sector, providing repair services and selling spare parts for two-wheeled vehicles. At this time the sales system that runs at the Mandala Motor Workshop is still manual in making business records, there are often mistakes when dividing the entire payment, there’s no recording of client information, recording inventory of goods written on paper notes, resulting risk of loss and inefficiency. Point of Sales (POS) is system can help the marketing business process of mandala motor repair shop. Each Point of Sales consists of hardware and applications, these 2 parts used for running business process. System design using Agile Development Method has six stages consisting of planning, implementation, testing, documentation, deployment, and maintenance. Aimed assisting management in checking marketing reports directly, making easier for industry to carry out marketing business, inventory, client information and producing good communication for companies, employees, clients. This application has also been evaluated using the Software Usability Scale (SUS) method, where the average of 200 respondents, namely 76.6%, is included in the acceptable application acceptance level category, the grade level category is in position C, and the adjective rating category be in position. acceptable so that it can be concluded that the application is suitable for use by users and has been fulfilled.